Buried in the country - Dunn, Carola (Dunn, Carola. Cornish mysteries., 2016)
"After many years working around the world for an international charity in the late 1960s, Eleanor Trewynn has retired to the relative quiet of a small town in Cornwall. But her quiet life is short-lived when, due to her experience, the Commonwealth Relations Office reaches out to her to assist in a secret conference that is to take place in a small hotel outside the historical village of Tintagel. Meanwhile, her niece, Detective Sargent Megan Pencarrow, is investigating the disappearance of a local solicitor when she is assigned to help provide security for the conference. Two African students, refugees from Ian Smith's Rhodesia, arrive for the conference, escorted by Megan's bê̂te noire from Scotland Yard. They are followed by two mysterious and sinister Londoners, whose allegiances and connections to the conference and the missing solicitor are unclear. With a raging storm having trapped everyone in the hotel, the stage is set for murder, and it's up to Eleanor and Megan to uncover the truth before more lives are lost"--